Analysis Of Effects Of Fruits In Medical Studies: A Study On Malay Malay Communities - Muhammad, S.J.N, Jelani, J. P, Rahman, N.S.A, Abd Rahman, M.M, Puteh, C. N. C, Rahim, A.A (International Journal of Modern Agriculture, 2021)
This study that pertains to medical studies which is a Malay heritage from their ancestors in the field of culture. This is because the community is also known as a society that is rich with knowledge such as a method of making medicine, treating, preparing materials, acquiring knowledge from the range up to the cultivation of plants for medicinal purposes. Thus, the objective of this study is to analysis and discuss of effects of fruits in medical studies. This study also uses Medical Anthropology by Hashim Awang A.R (1990) as a reinforcement of this study. Findings have shown that limes are most widely used to treat diseases in Kitab Tib Muzium Terengganu. The use of fruits for medicinal purposes in this medical studies’ text is influenced by several factors such as belief in the animism and physicality of fruits that are often associated with nature and human life. Accordingly, this study is hoped to benefit researchers who are researching on Malay medical studies.